Enhancing Career Maturity in Students Through Career Services at Laboratory Senior Highschool UM - Nasywa, Kirana Ardisya; Putri, Thesalonica Bona; Muslihati, Muslihati; Saptaningsasi, Agustina; Hanafi, Husni (Universitas Negeri Malang, 2024)
Career maturity had been explored as one of essential variable in career planing, career path, and especially career decision-making. Highschool students had various issues that hinder their career maturity. This research aims to evaluate the effectiveness of career services at Laboratory Senior Highschol UM in enhancing students' career maturity. A quasi-experimental one-group pretestposttest design was employed. The sample were 32 students purposively selected class XI, assessed using a student career maturity questionnaire. The findings revealed that 27 students demonstrated significant improvement in career maturity following the career services intervention. These results highlight the overall success of the career services in fostering student career maturity. However, some students may require individualized support to further develop their career maturity. There are various issues that could help develop career maturity in specific, like career self-efficacy, career aspiration, and career palnning skills, etc. The study recommends designing alternative strategies to complement career services, offering personalized assistance to students in their career development. Keywords: carreer maturity; career service; guidance and counseling, highschool career